2010
DOI: 10.1111/j.1365-3156.2010.02703.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of HIV on agricultural livelihoods in southern Uganda and the challenges of attribution

Abstract: SummaryChanges in agriculture and rural livelihoods in Africa are often attributed to the HIV epidemic. While acknowledging that the epidemic has devastated many families and communities because of excess morbidity and mortality, this review explores other causes of change in agriculture practices and production in southern Uganda. Over the past 20 years labour shortages, because of labour migration and changing aspirations (as well as HIV), crop and livestock pests and diseases, declining soil fertility, chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 88 publications
1
12
0
Order By: Relevance
“…Rakai is especially vulnerable to flood events (Onyango et al, 2012). HIV/ AIDS seriously impacts food security in the area (Hunter, Bulirwa, & Kisseka, 1993;Taylor et al, 2011). Subsistence agriculture is the dominant economic activity.…”
Section: Ugandamentioning
confidence: 99%
“…Rakai is especially vulnerable to flood events (Onyango et al, 2012). HIV/ AIDS seriously impacts food security in the area (Hunter, Bulirwa, & Kisseka, 1993;Taylor et al, 2011). Subsistence agriculture is the dominant economic activity.…”
Section: Ugandamentioning
confidence: 99%
“…There is evidence from research that many households in the study area in rural Uganda are increasingly growing cereals, legumes and tubers such as maize, beans, cassava, sweet potatoes and groundnuts [25]. Examples from other settings have shown that crops such as maize and groundnuts are prone to severe infestations by aflatoxin-producing fungi, leading to contamination and compromising food quality [6,8,20,[26][27][28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the respondents were seeking partners without children. This is probably because individuals with children may have high HIV and AIDS prevalence compared from individuals without children due to greater exposure via unprotected sex with partners who may have higher rates of infection [36,37].…”
Section: Discussionmentioning
confidence: 99%